1999
DOI: 10.1083/jcb.144.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Homologue of the Caenorhabditis elegans UNC-76 Protein Involved in Axonal Outgrowth Is a Protein Kinase C ζ–interacting Protein

Abstract: By the yeast two-hybrid screening of a rat brain cDNA library with the regulatory domain of protein kinase C ζ (PKCζ) as a bait, we have cloned a gene coding for a novel PKCζ-interacting protein homologous to the Caenorhabditis elegans UNC-76 protein involved in axonal outgrowth and fasciculation. The protein designated FEZ1 (fasciculation and elongation protein zeta-1) consisting of 393 amino acid residues shows a high Asp/Glu content and contains several regions predicted to form amphipathic helices. Norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(101 citation statements)
references
References 56 publications
0
101
0
Order By: Relevance
“…The interaction of DISC1 with FEZ1 in PC12 cells was markedly enhanced by exposure to NGF, along with neurite extension, 11,14 whereas PACAP had no effect (our unpublished observation). On the other hand, PACAP caused a marked, but transient, decrease of association between DISC1 and DBZ in PC12 cells ( Figure 3c) and NGF had a similar effect (data not shown).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The interaction of DISC1 with FEZ1 in PC12 cells was markedly enhanced by exposure to NGF, along with neurite extension, 11,14 whereas PACAP had no effect (our unpublished observation). On the other hand, PACAP caused a marked, but transient, decrease of association between DISC1 and DBZ in PC12 cells ( Figure 3c) and NGF had a similar effect (data not shown).…”
Section: Discussionmentioning
confidence: 71%
“…11 The interaction of DISC1 with FEZ1 was markedly enhanced along with neurite extension in PC12 cells by nerve growth factor (NGF) stimulation. 11,14 An association between singlenucleotide polymorphisms of the FEZ1 gene and schizophrenia has also been suggested in a Japanese population. 15 Kendrin, also termed pericentrin-B, is a calmodulin-binding protein that is specifically localized to the centrosome, and we have previously demonstrated that Kendrin is involved in the centrosomal localization of DISC1.…”
Section: Introductionmentioning
confidence: 99%
“…FEZ1 is reported to be involved in axonal outgrowth and fasciculation, 21,22 and we have shown that FEZ1 colocalizes with F-actin. Reorganization of the actinbased cytoskeletal structure is required for the neurite outgrowth of neurons.…”
Section: Disc1 Participates In Neurite Outgrowth Through Its Interactmentioning
confidence: 97%
“…We raised an antibody against FEZ1 which detected a protein of (Figure 4p), the size revealed by in vitro synthesis. 22 DISC1 exhibited a punctate distribution in the cytosol of SK-N-SH cells with the perinuclear high-density region (Figure 4a). DISC1 was also located on some filamentous structures which overlapped with F-actin as stress fibers detected by phalloidin staining (Figure 4a-c).…”
Section: Intracellular Localization Of Disc1 and Fez1mentioning
confidence: 99%
See 1 more Smart Citation